Fatalities related to lightning occurrence and agriculture in Bangladesh. (December 2019) - Holle, Ronald L.; Dewan, Ashraf; Said, Ryan; Brooks, William A.; Hossain, Md. Faruk; Rafiuddin, M.
Abstract: Large numbers of Bangladesh lightning fatalities during the pre-monsoon season have resulted in speculation about causes for this annual event. The present study addresses the situation with lightning occurrence, lightning fatality, and agricultural data. Of the 1, 434 lightning deaths from 2013 to 2017 in Bangladesh, an average of 1.73 deaths occur per day in the pre-monsoon season, 0.71 in the monsoon, and very small averages in other seasons. More than half of the deaths are related to agriculture. Population-weighted fatality rates are large in several northeastern districts. Lightning fatalities are frequent in April and especially May during both morning and afternoon. Based on 37.2 million strokes from the Global Lightning Dataset GLD360 network over Bangladesh from 2013 to 2017, lightning is also most frequent in the northeast from mid-April through early June at all hours of the day. Several districts with large lightning stroke densities and fatality rates are the same as with the greatest farming participation. A common crop is Boro rice harvested during April and May in several districts with frequent lightning. As a result, temporal and spatial connections exist among lightning fatalities and occurrence, and agricultural workers. This study identifies the lightning fatality maximum during the pre-monsoon season as frequent lightning coincident with labor-intensive agricultural practices in specific locations. As a result, measures can be taken to address the underlying lightning vulnerability. Additionally, agricultural studies at the times and locations identified here need further exploration. The final steps are to provide meteorological warnings and lightning-safe locations for the most vulnerable population. Graphical abstract: Image 1 Highlights: Lightning fatalities and occurrence peak in pre-monsoon months from mid-April to June. Lightning fatalities and occurrence are most frequent in northeast districts. Farming accounts for more than half of all lightning fatalities, often during Boro rice harvesting. Lightning fatalities and occurrence are nearly as frequent in the morning as in afternoon.